Effect of Variable Thermal Conductivity on Buoyant Convection in a Cavity with Internal Heat Generation - Sivasankaran, S. (Nonlinear Analysis: Modelling and Control, 2007)
A numerical study has been made to analyze the effects of variable thermal conductivity on the natural convection of heat generating fluids contained in a square cavity with isothermal walls and the top and bottom perfectly insulated surfaces. The flow is assumed to be two-dimensional. Calculations are carried out by solving governing equations for different parameters. The flow pattern and the heat transfer characteristics inside the cavity are presented in the form of steady-state streamlines, isotherms and velocity profiles. The heat transfer rate is increased by an increase in the thermal conductivity parameter.